Characterization, thermal and electrical properties of aminated PVC/oxidized MWCNT composites doped with nanographite - Haruna, Hassan; Pekdemir, Mustafa Ersin; Tukur, Abdulrahman; Coskun, Mehmet (Springer, 2020)
The composites were prepared with PVC modified with 3-(dimethylamino)-1-propylamine (aminated PVC) and MWCNT containing 2.5% carboxyl group (oxidized MWCNT) and doped with nanographite in different percentages (1, 5, 8 and 12% by mass). Thermal investigation was performed from DSC and TGA curves. From the DSC curves, it was observed that T-g temperature of aminated PVC increased with the increase in oxidized MWCNT content. At the composite containing 5% MWCNT, T-g temperature of aminated PVC decreased slightly with increasing nanographite, at the composite containing 11% MWCNT increased slightly and at the composite containing 8% MWCNT nearly fixed. While according to initial decomposition temperature doping with nanographite did not affect significantly the thermal stability of composites, the amount of residue at 500 degrees C increased some with doping. Conductivity was only investigated for aminated PVC/8% oxidized MWCNT/8% nanographite composite. Doping with nanographite significantly increased the conductivity of the composite. (Conductivity increased values from 10(-8)-10(-9) S cm(-1) to 10(-4) S cm(-1)). The conductivity increased with increasing temperature at all frequencies. Conductivity-related activation energies were calculated at different frequencies, and while the frequency increased from 630 to 29,500 Hz, the activation energy decreased from 0.0228 to 0.0193 eV.
2nd International Conference on Physical Chemistry and Functional Materials (PCFM) -- JUN 25-27, 2019 -- Cappadocia, TURKEY
Keywords: PVC; MWCNT; Nanographite; Thermal; Conductivity